Unexpected encounters: The surprising link between ovarian cancer and axillary lymphadenopathy - Marina Balbino; Federica Masino; Manuela Montatore; Francesca Anna Carpagnano; Giuseppe Guglielmi (Radiology Case Reports)
Ovarian tumors represent a significant health concern for women, often leading to morbidity and mortality. We present the case of a 46-year-old patient without notable personal or family history of tumors, who initially presented with bilateral axillary lymphadenopathy. Given the clinical presentation and suspicion of a Cancer of Unknown Primary (CUP) syndrome, the patient underwent imaging examination, such as ultrasound of the axilla, mammography, and breast magnetic resonance imaging. The axillary tru-cut biopsy histological examination revealed ovarian metastasis. The total body computed tomography (CT) scan and pelvic MRI confirmed the presence of a left ovarian tumor. The patient underwent surgical intervention with excision of the tumor and axillary lymph node dissection. Histological analysis confirmed the diagnosis of high-grade serous ovarian carcinoma. The patient was initiated on adjuvant chemotherapy and a long-term follow-up was scheduled. This case underscores the importance of comprehensive diagnostic evaluation in patients presenting with suspicious symptoms, such as axillary lymphadenopathy, to ensure timely and appropriate management of ovarian carcinoma and related conditions.